Matricellular Proteins in the Trabecular Meshwork: Review and Update - Chatterjee, Ayan (Mary Ann Liebert, Inc., 2014)
Primary open-angle glaucoma (POAG) is a leading cause of blindness worldwide, and intraocular pressure (IOP) is an important modifiable risk factor. IOP is a function of aqueous humor production and aqueous humor outflow, and it is thought that prolonged IOP elevation leads to optic nerve damage over time. Within the trabecular meshwork (TM), the eye's primary drainage system for aqueous humor, matricellular proteins generally allow cells to modulate their attachments with and alter the characteristics of their surrounding extracellular matrix (ECM). It is now well established that ECM turnover in the TM affects outflow facility, and matricellular proteins are emerging as significant players in IOP regulation. The formalized study of matricellular proteins in TM has gained increased attention. Secreted protein acidic and rich in cysteine (SPARC), myocilin, connective tissue growth factor (CTGF), and thrombospondin-1 and -2 (TSP-1 and -2) have been localized to the TM, and a growing body of evidence suggests that these matricellular proteins play an important role in IOP regulation and possibly the pathophysiology of POAG. As evidence continues to emerge, these proteins are now seen as potential therapeutic targets. Further study is warranted to assess their utility in treating glaucoma in humans.